Selenium-speciation experiments from soil samples by accept of ionchromatography-inductively coupled plasma mass spectrometry (IC-ICP-MS) method - Széles, Éva; Kovács, Béla; Prokisch, József; Győri, Zoltán (Acta Agraria Debreceniensis, 2006)
In these days, selenium is one of the most investigated microelements. It has an important proven role in many vital processes. Selenium deficiency can play a role in the contraction of many diseases (e.g. cancer, heart diseases, etc.) and in the aggravation of their clinical aspect directly or indirectly. In this paper, we study the soil samples of an outdoor experiment for the conversion of the inorganic selenium salt that was spread out in different doses. The danger of the wash-out effect was also investigated. Our experiments showed, that most of the inorganic selenite transforms to selenate form during the years, and in this selenate form it moves to the deeper layers of soil.